THE STRATEGY OF INDONESIAN MINISTRY OF TOURISM IN WONDERFUL INDONESIA’S BRANDING THROUGH SOCIAL MEDIA - Denny Prawibowo; Oktaviana Purnamasari (Universitas Muhammadiyah Jakarta, 2019)
Currently, the rise of social media with various platforms has experienced a giant leap. The high demands of information accessed quickly by the community through social media becomes a certain concern for the Indonesian Ministry of Tourism to use social media as a tool in promoting and building Indonesian tourism brands. Social media is also seen as having potential benefit to increase tourism sector and strengthen Wonderful Indonesia's branding quickly and precisely. This study aims to determine the strategy of the Ministry of Tourism on Wonderful Indonesia branding through social media, find out the types of social media used and identified Wonderful Indonesia's branding strategies related to planning and positioning, program design, performance and maintaining brand equity in the context of social media. The theory used in this study is Social Media theory and Strategic Brand Management theory by Kevin Keller, including identifying and developing brand plans, designing and implementing brand marketing programs, measuring and interpreting brand performance, and growing and maintaining brand equity. The approach used in this study is qualitative with descriptive method. For data collection techniques, we used depth interviews with key informan of the Ministry of Tourism, and key informan of social media‟s followers. Observations were also made on social media used by the Ministry of Tourism, namely Facebook, Instagram, Twitter, Youtube and Googleplus. Results of this study indicated that tourism's strategy in Wonderful Indonesia's branding through social media was carried out in several stages; the first stage was planning. In 2015, re-branding was conducted with the addition of typography and touches on Wonderful Indonesia‟s logo. Then the second stage was the design of the program by placing the right positioning for each Indonesian tourism destination which includes three elements of tourism products, namely natural, cultural and man-made with marketing strategy programs that are carried out namely BAS (Branding, Advertising and Selling) which refers in major cities of the world such as Berlin, New York, Amsterdam, Madrid and Paris. The third stage was the performance of the Ministry of Tourism, which according to the Central Agency Statistics, foreign tourist arrivals to Indonesia in 2017 increased rapidly to 14.4 million tourists. In addition, another proof of performance was Wonderful Indonesia's physical branding ranked 42nd in 2018 set by the World Economy Forum. The fourth stage was to grow and maintain brand equity. This was achieved by Wonderful Indonesia by gaining 46 awards in 22 countries in 2016. Then in 2017 Wonderful Indonesia received 27 awards in 13 countries, whether in 2018 won